Replication of Synthetic Defective Interfering RNAs Derived from Coronavirus Mouse Hepatitis Virus-A59 - LUYTJES, WILLEM (Virology, 1996)
We have analyzed the replication of deletion mutants of defective interfering (DI) RNAs derived from the coronavirus mouse hepatitis virus (MHV)-A59 in the presence of MHV-A59. Using two parental DI RNAs, MIDI and MIDIΔH, a twin set of deletion mutants was generated with progressively shorter stretches of 5′ sequence colinear with the genomic RNA. All deletion mutants contained in-frame ORFs. We show that in transfected cells and after one passage the DI RNAs were detectable and that their accumulation was positively correlated with the length of 5′ sequence they contained. However, accumulation of two twin mutants, Δ2, in which sequences from nucleotide position 467 were fused to those from position 801, was undetectable. In passage 4 cells, but not in transfected or in passage 1 cells, recombination with genomic RNA led to the appearance of the parental DI RNAs. The accumulation of these parental RNAs was inversely correlated with the length of 5′ sequence on the deletion mutants and was highest in the Δ2 samples. In sharp contrast to the data reported for MHV-JHM-derived DI RNAs, we show that MHV-A59-derived mutant RNAs do not require an internal sequence domain for replication. The data suggest that coronavirus replication involves an RNA superstructure at the 5′ end of the genome or one comprising both ends of the genomic RNA. We also conclude from the recombination data that in-frame mutants with impaired replication signals are more fit than out-frame mutants with intact replication signals.